Portable Coffin Lowering Device for COVID-19 Corpse Handling: Education, Design Process, and Strength Analysis - Asriyanti, A.; Septiani, Tasya Diana; Siagian, Michael Soritua Putrapratama; Triawan, Farid (Universitas Pendidikan Indonesia (UPI), 2021)
With the growing rate of the COVID-19 case that has not decreased significantly, healthcare workers are required to work extra both in the hospital and for the corpses' funeral process. Since the corpse condition is different from a normal corpse, the treatment must also be different. The objective of this paper is to propose a portable device as an education tool that can ease the burial process of COVID-19 corpse. This device can be operated by only two people, and the load is bearable because there is a worm gear system that helps the pulley system. Other supporting features will be explained in this paper. Theoretical strength analyses are conducted under static and fatigue loading. From the static case, based on the Maximum Shear Stress failure criterion, the safety factors on the critical parts are 1.28 and 5.67. Then, fatigue strength analysis is conducted to provide life prediction for this device. As a result, the fatigue safety factors are found to be greater than 1. These findings indicate that the proposed design is appropriate for real-world use and can be further studied for manufacturing.